Novel methyl substituted 1-(5, 6-dihydro-[1, 2, 4]triazolo[4, 3-a]pyrazin-7(8H)-yl)methanones are P2X7 antagonists. Issue 16 (15th August 2015) - Rudolph, Dale A.; Alcazar, Jesus; Ameriks, Michael K.; Anton, Ana Belen; Ao, Hong; Bonaventure, Pascal; Carruthers, Nicholas I.; Chrovian, Christa C.; De Angelis, Meri; Lord, Brian; Rech, Jason C.; Wang, Qi; et al.
Graphical abstract